Workplace sitting and height-adjustable workstations: A randomized controlled trial - Neuhaus, M.; Healy, Genevieve; Dunstan, D.; Owen, N.; Eakin, E. (2014)
Background: Desk-based office employees sit for most of their working day. To address excessive sitting as a newly identified health risk, best practice frameworks suggest a multi-component approach. However, these approaches are resource intensive and knowledge about their impact is limited. Purpose: To compare the efficacy of a multi-component intervention to reduce workplace sitting time, to a height-adjustable workstations-only intervention, and to a comparison group (usual practice). Design: Three-arm quasi-randomized controlled trial in three separate administrative units of the University of Queensland, Brisbane, Australia. Data were collected between January and June 2012 and analyzed the same year. Setting/participants: Desk-based office workers aged 20-65 (multi-component intervention, n=16; workstations-only, n=14; comparison, n=14). Intervention: The multi-component intervention comprised installation of height-adjustable workstations and organizational-level (management consultation, staff education, manager e-mails to staff) and individual-level (face-to-face coaching, telephone support) elements. Main outcome measures: Workplace sitting time (minutes/8-hour workday) assessed objectively via activPAL3 devices worn for 7 days at baseline and 3 months (end-of-intervention).Results: At baseline, the mean proportion of workplace sitting time was approximately 77% across all groups (multi-component group 366 minutes/8 hours [SD=49]; workstations-only group 373 minutes/8 hours [SD=36], comparison 365 minutes/8 hours [SD=54]). Following intervention and relative to the comparison group, workplace sitting time in the multi-component group was reduced by 89 minutes/8-hour workday (95% CI=-130, -47 minutes; p<0.001) and 33 minutes in the workstations-only group (95% CI=-74, 7 minutes, p=0.285). Conclusions: A multi-component intervention was successful in reducing workplace sitting. These findings may have important practical and financial implications for workplaces targeting sitting time reductions. Clinical Trial Registration: Australian New Zealand Clinical Trials Registry 00363297.